SEJARAH TAMBANG BATU BARA OMBILIN SAWAHLUNTO PADA MASA PEMERINTAHAN BELANDA (1891-1942) - Cyndi Dwi Rahmadani; Isjoni Isjoni; Tugiman MS Tugiman MS (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Indonesia is one of the countries with a lot of natural resources. One of Indonesia's natural wealth is coal. The potential of coal resources in Indonesia are in Kalimantan, Sumatra, Java, Sulawesi and Papua. Coal in Sumatra one of them is in West Sumatra, around Batang Ombilin, Sawahlunto. The purpose of this study is to (1) Describe the initial stages of exploration and exploitation of coal mine Ombilin Sawahlunto. (2) Describe the background of the workers involved in extracting the Ombilin coal mine in Sawahlunto. (3) Knowing the life of coal miner Ombilin Sawahlunto. The research method used by the writer is historical method, with qualitative descriptive approach, and using data collection techniques such as literature study, observation, interview and documentation. Coal was first discovered in West Sumatra precisely in Padang Sibusuk discovered by Ir. C. De Groot, while the coal around Batang Ombilin was discovered by Ir. W.H. De Greve. Mining method used in the Dutch era is deep minning with sandfilling system. Coal in Sawahlunto has depth and layers of different layers. The miners are divided into forced, contracted and free laborers. Facilities obtained by miners are housing, clothing, food, and health insurance. Currently the Ombilin coal mine is still there, only the process is being suspended.Key Words: History, Ombilin Coal, Mining Methods, Mine Workers